STATE REGULATION OF THE QUALITATIVE DEVELOPMENT OF THE NATIONAL EDUCATION SYSTEM IN UKRAINE - Dombrovska S.M. (Pressing Problems of Public Administration, 2015)
Dominant course of our country towards market economy determines the necessity to reform the higher education system as a principle factor to bring up overwhelmed personality, to expand individual approach in development of creative abilities, to improve the up-bringing of competent specialist in different social spheres.